Harnblase: Tumorvorstufen und nichtinvasive Karzinome - Lange, Fabienne; Hartmann, Arndt; Eckstein, Markus (Die Pathologie, 2024)
Background: In recent years, our understanding of the genesis and development of urothelial carcinomas (UC) has expanded considerably thanks to advancing molecular classifications. These advances have led to significant changes in the 5th edition of the WHO classification of tumors of the urinary tract and male genitalia. The new findings allow both the introduction of modern diagnostic approaches and a return to proven methods in the evaluation of precursor lesions and non-invasive carcinomas. Aims: This article is intended to provide a summarized overview of the various precursor lesions and pathways of urothelial carcinoma. Results and discussion: The changes and clarifications in the 5th edition of the WHO classification reflect the progress made in the molecular and morphological characterization of urothelial carcinomas. These adjustments provide an improved basis for diagnosis and treatment and emphasize the importance of differentiated molecular profiles for the classification and treatment of UC. Despite all this, conventional histology remains the gold standard for the diagnosis and classification of non-invasive carcinomas and precursor lesions.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Carcinoma in situ; Immunohistochemistry; Papillary carcinoma; Prognosis; Transitional cell carcinoma